Economical Production of Xylitol from Candida magnoliae TISTR 5663 Using Sugarcane Bagasse Hydrolysate - Wannawilai, Siwaporn; Sirisansaneeyakul, Sarote (Agriculture and Natural Resources, 2015)
Xylitol is a popular sweetener in food, pharmaceutical and oral hygiene products due to its many advantages for health such as preventing tooth decay and suitability for diabetes patients. In this research, economical production of xylitol was obtained using the high-xylitol-producing, osmotolerant yeast, Candida magnoliae TISTR 5663, compared with two lower cost culture media (0.15 and 0.64 USD.L-1) with the defined medium for C. magnoliae TISTR 5663 (approximately 1 USD.L-1). Among these media, the specific growth rates, xylitol yields and productivities obtained were not significantly different (P > 0.05, 0.001 and 0.001, respectively). Thus, the cheapest minimal medium with (NH4)2HPO4 as the nitrogen source (0.15 USD.L-1) was used for the production of xylitol from sugarcane bagasse hydrolysate as a carbon source. It was found that C. magnoliae TISTR 5663 gave a noticeably xylitol yield and productivity of 0.295 g.g-1 and 0.024 g.L-1.hr-1, respectively. This indicated that the culture medium containing these inexpensive carbon and nitrogen sources was feasible for lowering the production cost of xylitol. In addition, the xylitol production was modeled using either xylose or sugarcane bagasse hydrolysate as the main carbon source. The model fitted well with the observations for cell growth, xylose consumption and xylitol production from xylose as a carbon source, but was less suitable using the sugarcane bagasse hydrolysate data.